2019
DOI: 10.1177/1071100719867942
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Effects in Foot and Ankle Surgery: An Evidence-Based Review

Abstract: Background: The purpose of this article was to review the basic science pertaining to the harmful effects of cigarette smoke, summarize recent clinical outcome studies, and examine the benefits of smoking cessation and the efficacy of current smoking cessation strategies. Methods: The literature concerning basic science, clinical outcomes, and smoking cessation was reviewed; over half (56%) of the 52 articles reviewed were published in the last 5 years. Results: Smoking is associated with low bone mineral dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…However, Matsuoka K believed that the length of time to quit smoking before surgery had no relationship with the frequency of PCCs, even if smoking restarted within two weeks before surgery. Related studies also found that LSHS before surgery was more correlated with postoperative complications of foot and ankle surgery, adult spinal deformity surgery, and head and neck microvascular reconstruction surgery than those who had never smoked [23,24,43].…”
Section: Discussionmentioning
confidence: 90%
“…However, Matsuoka K believed that the length of time to quit smoking before surgery had no relationship with the frequency of PCCs, even if smoking restarted within two weeks before surgery. Related studies also found that LSHS before surgery was more correlated with postoperative complications of foot and ankle surgery, adult spinal deformity surgery, and head and neck microvascular reconstruction surgery than those who had never smoked [23,24,43].…”
Section: Discussionmentioning
confidence: 90%
“…It is well-known that smoking is related to the increase of risk of several diseases, including the impairment of skin wound healing, with studies proving that cigarette compounds like tobacco, nicotine, carbon monoxide, and hydrogen cyanide affect the mechanisms of healing [ 48 ]. Hypoxia is one of the major mechanisms for smoking-related impairment of wound healing, decreasing the proliferation of erythrocytes, oxygenation, blood flow, and angiogenesis in wounded tissue [ 34 ].…”
Section: Factors That Affect the Wound Healingmentioning
confidence: 99%
“…9,18 Smoking is also a relative contraindication to surgery and is associated with increased wound complications, delayed union following osteotomy and poorer patient-reported outcomes. [19][20][21] Smoking cessation should be strongly encouraged.…”
Section: Operative Managementmentioning
confidence: 99%